Dialectology and Linguistic Geography - (:unkn) unknown (My University, 2020)
Both dialectology and linguistic geography study language variation, change, and diffusion. The former examines geolinguistic data synchronically and diachronically on an intragenetic level (e.g. Bantu, Berber) or an intergenetic phylum level (e.g. Niger-Congo, Afro-Asiatic), whereas the latter focuses on stable, contact-induced linguistic changes on an intergenetic phylum level in adjacent areas.In the present chapter, I address these linguistic disciplines from an African perspective, explaining their fundamental principles by means of specific African-related cases. Furthermore, I compare the different approaches to African areal linguistics, pointing out theirrespective potentials and limitations. This introduction is followed by a preliminary explanation of the dialectological framework, problematizing some of its theoretical and methodological concepts, such as “dialect consciousness”, “inter-intelligibility”, “language continuum”, and the “language versus dialect” dichotomy (section 7.2). In the same section, a detailed dialectometry classification and its various methods are presented. In section 7.3, a critical overview of the existing studies in African areal classification is given. The chapter ends with a number of conclusions about language variation and its connection with language diffusion and evolutionwith respect to the African area (section 7.4).
Keywords: African Research